Macrophage migration inhibitory factor as a potential predictor for requirement of renal replacement therapy after orthotopic liver transplantation. Issue 5 (May 2015) - Stefaniak, Joanna; Schiefer, Judith; Miller, Edmund John; Krenn, Claus Georg; Baron, David Marek; Faybik, Peter
Abstract : Acute kidney injury (AKI) after orthotopic liver transplantation (OLT) is associated with a poor clinical outcome. Because there is no specific treatment for postoperative AKI, early recognition and prevention are fundamental therapeutic approaches. Concentrations of the proinflammatory cytokine macrophage migration inhibitory factor (MIF) are elevated in patients with kidney disease. We hypothesized that plasma MIF concentrations would be greater in patients developing AKI after OLT compared with patients with normal kidney function. Twenty‐eight patients undergoing OLT were included in the study. Kidney injury was classified according to AKI network criteria. Fifteen patients (54%) developed severe AKI after OLT, 11 (39%) requiring renal replacement therapy (RRT). On the first postoperative day, patients with severe AKI had greater plasma MIF concentrations (237 ± 123 ng/mL) than patients without AKI (95 ± 63 ng/mL; P  < 0.001). The area under the receiver operating characteristic (ROC) curve for predicting severe AKI was 0.87 [95% confidence interval (CI), 0.69‐0.97] for plasma MIF, 0.61 (95% CI, 0.40‐0.79) for serum creatinine (sCr), and 0.90 (95% CI, 0.72‐0.98) for delta serum creatinine (ΔsCr). Plasma MIF ( P  = 0.02) and ΔsCr ( P  = 0.01) yielded a better predictive value than sCr for the development of severe AKI. Furthermore, the area under the ROC curve to predict the requirement of RRT was 0.87 (95% CI, 0.68‐0.96) for plasma MIF, 0.65 (95% CI, 0.44‐0.82) for sCr, and 0.72 (95% CI, 0.52‐0.88) for ΔsCr. Plasma MIF had a better predictive value than sCr for the requirement of RRT ( P  = 0.02). In conclusion, postoperative plasma MIF concentrations were elevated in patients who developed severe AKI after OLT. Furthermore, plasma MIF concentrations showed a good prognostic value for identifying patients developing severe AKI or requiring postoperative RRT after OLT. Liver Transpl 21:662–669, 2015 . © 2015 AASLD.